Power generation distribution, applications and implications - Marini, Lauren (Clanrye International, 2015)
The distribution, applications as well as implications of power generation are described in this book. The consumption of renewable energy sources such as wind energy or solar energy is currently of great interest. Nevertheless, since their availability is sporadic and unstable, this can lead to frequency variation, grid instability and total or partial loss of load power supply. This reason keeps them far from being appropriate sources to be directly connected to the main utility grid. Also, the availability of a static converter as output unit of the generating plants brings voltage and current harmonics into the electrical system which causes a negative result on system power quality. By integrating distributed power generation systems closed to the loads in the electric grid, we can get rid of the need to transfer energy over long distances through electric grid. This book discusses different power generation and distribution systems with an evaluation of some types of existing disturbances and a study of distinct industrial applications such as battery charges.